Evaluation of volumetric modulated arc therapy technique for cranio-spinal irradiation: A rando - phantom based dosimetric study - Goksel, E. O.; Tezcanli, E.; Okutan, M.; Bilge, H.; Yarar, Y. Yildiz (IJRR-IRANIAN JOURNAL RADIATION RES, 2021)
Background: In this study, clinical advantages and the dosimetric accuracy of volumetric modulated arc therapy (VMAT) technique for cranio-spinal irradiation (CSI) were investigated and compared with field in field (FinF) and intensity modulated radiotherapy (IMRT) techniques. Materials and Methods: The organs at risk (OARs) and planning target volume (PTV) were generated on the RANDO phantom computerized tomography (CT) image series. The dose-volume parameters for PTVs and OARs were compared for three techniques. Furthermore, the dose distribution inside the RANDO phantom was measured with thermoluminescent dosimeter (TLD) for all three techniques. Comparisons were done between measured and calculated doses of field junctions, targets and OARs. Results: FinF failed to obtain an adequate dose distribution for the upper spine (US), while VMAT and IMRT provided good dose coverage for all parts of the PTV. The most homogeneous dose distribution at the field junctions was obtained with the VMAT. Although heart, thyroid, intestine, lung, liver and testicular maximum doses were lower for the VMAT, the mean doses were higher except for the heart and thyroid. The absolute volume receiving prescription dose was significantly lower for the VMAT. The median differences between the TLD measurements and TPS calculations were 0.27% (7.8, -9.7; p=0.394), -0.28% (8.1, -10.7; p=0.322) and 0.33% (8.4, -12; p=0.338) for the FinF, IMRT and VMAT, respectively. These differences were not found statistically significant for the VMAT technique, as were the other two techniques. Conclusion: We conclude that the VMAT technique is the optimal Linac based CSI treatment in regards to dose coverage, dose homogeneity in field junctions and OAR sparing for higher doses. In addition, the VMAT showed dose distribution accuracy as good as the two other techniques in measurements simulating real clinical situations.
Keywords: Cranio-spinal irradiation; VMAT; TLD; RANDO phantom; RADIATION-THERAPY; DOSE DISTRIBUTION; RADIOTHERAPY; PHOTON; IMRT; ALGORITHM; CANCER; SUPINE; RISK; VERIFICATION; Radiology, Nuclear Medicine & Medical Imaging